2017
DOI: 10.1002/jbm.a.36061
|View full text |Cite
|
Sign up to set email alerts
|

Silicates in orthopedics and bone tissue engineering materials

Abstract: Following the success of silicate-based glasses as bioactive materials, silicates are believed to play important roles in promoting bone formation and have therefore been considered to provide a hydroxyapatite (HAP) surface layer capable of binding to bone as well as potentially being a pro-osteoinductive factor. Natural silicate minerals and silicate-substituted HAPs are also being actively investigated as orthopaedic bone and dental biomaterials for application in tissue engineering. However, the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 112 publications
(245 reference statements)
0
32
0
Order By: Relevance
“… 71 Si is one of the most important trace elements in the human body, and its content reaches 100 ppm in bones and 200–550 ppm in the ECM. 72 Si is commonly absorbed in the form of metasilicate, which is widely distributed in connective tissue. 73 Si plays an important role in bone calcification and is beneficial for improving bone density and preventing osteoporosis.…”
Section: Main Types Of Bone Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“… 71 Si is one of the most important trace elements in the human body, and its content reaches 100 ppm in bones and 200–550 ppm in the ECM. 72 Si is commonly absorbed in the form of metasilicate, which is widely distributed in connective tissue. 73 Si plays an important role in bone calcification and is beneficial for improving bone density and preventing osteoporosis.…”
Section: Main Types Of Bone Biomaterialsmentioning
confidence: 99%
“… 73 Si plays an important role in bone calcification and is beneficial for improving bone density and preventing osteoporosis. 72 Especially in the early stage of osteogenesis, a high Si content in new bone can increase the degree of calcification to some extent, while a Si deficiency always causes bone distortion. 74 Some studies have shown that Si can not only promote the synthesis of collagen and proteoglycan but also activate bone-related gene expression and stimulate osteoblast proliferation and differentiation.…”
Section: Main Types Of Bone Biomaterialsmentioning
confidence: 99%
“…Si is essential for the metabolic process associated with bone calcification and is favorable for enhancing bone density and inhibiting osteoporosis. 22,23 Specifically, in the initial period of bone matrix calcification, Si contents in new bone can develop a certain degree of osteogenesis. 24 Aqueous Si was able to induce precipitation of inorganic phase of bone, ie, hydroxyapatite.…”
Section: Silica In Bone Metabolismmentioning
confidence: 99%
“…Today, silica is present in an impressive variety of everyday life products, such as glass and tableware, vitroceramics, domestic and industrial water membranes, plastics, paper, paints, silicones, semiconductors, fiber and optical glasses, electronic, optoelectronic, aerospace, and defense products [ 2 , 3 , 4 ], to mention some of them. As regards healthcare and medicine, SiO 2 is a current material in dentistry (tooth implants, ceramic pastes) [ 5 , 6 ], orthopedics (bone implants, scaffolds) [ 7 , 8 ], dermatology [ 9 ] and specialized medical devices (ophthalmological and bio-glasses, scaffolds) [ 10 , 11 , 12 , 13 ]. The coming of nanomedicine opened the door to new engineered materials/devices opportunities, colloidal silica having pride of place among micro and nanoparticles (NPs) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%